Myocardial Blood Flow and Flow Reserve in Patients With Acute Myocardial Infarction and Obstructive and Non-Obstructive Coronary Arteries: CZT SPECT Study - Zavadovsky, Konstantin V.; Vorobyeva, Darya A.; Mochula, Olga V.; Mochula, Andrew V.; Maltseva, Alina N.; Bayev, Andrew E.; Gulya, Marina O.; Gimelli, Alessia; Ryabov, Vyacheslav V. (Frontiers in Nuclear Medicine, 2022)
Background. To assess SPECT CZT derived myocardial blood flow (MBF) flow reserve (MFR) and flow difference (FD) in acute myocardial infarction (AMI) patients and to compare this data with serum cardiac troponin and cardiac magnetic resonance (CMR) findings. Methods. 31 AMI patients underwent invasive coronary angiography (ICA), serial high-sensitivity serum cardiac troponin I (cTnI) measurement, CZT SPECT with visual and quantitative (MBF, MFR and FD) perfusion parameters, and contrast-enhanced CMR. All AMI patients were divided into two groups: 1) with non-obstructive coronary arteries (MINOCA), n=10; 2) with obstructive coronary artery disease (MICAD), n=21. Results. The values of SSS and SRS were significantly (p<0.01) higher whereas global stress MBF, MFR significantly lower in MICAD patients as compared to MINOCA – 5.0 (3.0; 5.0) vs 9.0 (5.0; 13.0); 2.0 (1.0; 3.0) vs 6.0 (3.0; 11.0); 2.02 (1.71; 2.37) vs 0.86(0.72; 1.02) ml/min/g; and 2.61 (2.23; 3.14) vs 1.67 (1.1; 1.9), respectively. Stress MBF correlated with cTnI at 24h and day 4: =-0.39; p=0.03 and =-0.47; p=0.007, respectively. FD correlated with cTnI at 24h and day 4: =-0.39; p=0.03 and =-0.46; p=0.009. CMR analysis showed that infarct size, MVO and myocardial edema in MICAD patients were significantly (<0.05) higher as compared to MINOCA: 19.4 (10.4; 29.7) vs 1.8 (0.0; 6.9); 0.1 (0.0; 0.7) vs 0.0(0.0; 0.0) and 19.5 (12.0;30.0) vs 3.0 (0.0; 12.0), respectively. According to vessel-based analysis of CMR data, acute myocardial injury (defined as late gadolinium enhancement and myocardial oedema) was observed more frequently in MICAD patients compared to MINOCA: 34(37%) vs 5(5%) p=0.005, respectively. The values of regional stress MBF, MFR and FD were significantly decreased in LV territories characterized by myocardial injury compared to those without: 0.98 (0.73;1.79) vs 1.33 (0.94;2.08) p<0.01, 1.64 (1.0;2.36) vs 2.0 (1.53;2.89) p<0.01 and 0.33 (0.05;0.57) vs 0.56 (0.36;1.32) p>0.01, respectively. Conclusion. In patients with acute myocardial infarction, SPECT CZT derived flow measures were associated with the high-sensitivity troponin I as well as the extent of oedema, microvascular obstruction and infarct size detected by CMR. On the regional level, quantitative SPECT CZT measures were significantly lower in vessel territories characterized by myocardial injury.